Electron velocity of 6 × 107 cm/s at 300 K in stress engineered InAlN/GaN nano-channel high-electron-mobility transistors - Arulkumaran, S. (2015)
A stress engineered three dimensional (3D) Triple T-gate (TT-gate) on lattice matched In0.17 Al 0.83N/GaN nano-channel (NC) Fin-High-Electron-Mobility Transistor (Fin-HEMT) with significantly enhanced device performance was achieved that is promising for high-speed device applications. The Fin-HEMT with 200-nm effective fin-width (W eff) exhibited a very high I Dmax of 3940 mA/mm and a highest g m of 1417 mS/mm. This dramatic increase of I D and g m in the 3D TT-gate In0.17 Al 0.83N/GaN NC Fin-HEMT translated to an extracted highest electron velocity (v e) of 6.0 × 107 cm/s, which is ∼1.89× higher than that of the conventional In0.17 Al 0.83N/GaN HEMT (3.17 × 107 cm/s). The v e in the conventional III-nitride transistors are typically limited by highly efficient optical-phonon emission. However, the unusually high v e at 300 K in the 3D TT-gate In0.17 Al 0.83N/GaN NC Fin-HEMT is attributed to the increase of in-plane tensile stress component by SiN passivation in the formed NC which is also verified by micro-photoluminescence (0.47 ± 0.02 GPa) and micro-Raman spectroscopy (0.39 ± 0.12 GPa) measurements. The ability to reach the ve  = 6 × 107 cm/s at 300 K by a stress engineered 3D TT-gate lattice-matched In0.17 Al 0.83N/GaN NC Fin-HEMTs shows they are promising for next-generation ultra-scaled high-speed device applications.